Meta-organism gene expression reveals that the impact of nitrate enrichment on coral larvae is mediated by their associated Symbiodiniaceae and prokaryotic assemblages - Haoya Tong; Fang Zhang; Jin Sun; Shelby E. McIlroy; Weipeng Zhang; Yan Wang; Hui Huang; Guowei Zhou; Pei-Yuan Qian (Microbiome, 2023)
Abstract Background Coral meta-organisms consist of the coral, and its associated Symbiodiniaceae (dinoflagellate algae), bacteria, and other microbes. Corals can acquire photosynthates from Symbiodiniaceae, whilst Symbiodiniaceae uses metabolites from corals. Prokaryotic microbes provide Symbiodiniaceae with nutrients and support the resilience of corals as meta-organisms. Eutrophication is a major cause of coral reef degradation; however, its effects on the transcriptomic response of coral meta-organisms remain unclear, particularly for prokaryotic microbes associated with corals in the larval stage. To understand acclimation of the coral meta-organism to elevated nitrate conditions, we analyzed the physiological and transcriptomic responses of Pocillopora damicornis larvae, an ecologically important scleractinian coral, after 5 days of exposure to elevated nitrate levels (5, 10, 20, and 40 µM). Results The major differentially expressed transcripts in coral, Symbiodiniaceae, and prokaryotic microbes included those related to development, stress response, and transport. The development of Symbiodiniaceae was not affected in the 5 and 20 µM groups but was downregulated in the 10 and 40 µM groups. In contrast, prokaryotic microbe development was upregulated in the 10 and 40 µM groups and downregulated in the 5 and 20 µM groups. Meanwhile, coral larval development was less downregulated in the 10 and 40 µM groups than in the 5 and 20 µM groups. In addition, multiple larval, Symbiodiniaceae, and prokaryotic transcripts were significantly correlated with each other. The core transcripts in correlation networks were related to development, nutrient metabolism, and transport. A generalized linear mixed model, using least absolute shrinkage and selection operator, demonstrated that the Symbiodiniaceae could both benefit and cost coral larval development. Furthermore, the most significantly correlated prokaryotic transcripts maintained negative correlations with the physiological functions of Symbiodiniaceae. Conclusions Results suggested that Symbiodiniaceae tended to retain more nutrients under elevated nitrate concentrations, thereby shifting the coral-algal association from mutualism towards parasitism. Prokaryotic microbes provided Symbiodiniaceae with essential nutrients and may control Symbiodiniaceae growth through competition, whereby prokaryotes can also restore coral larval development inhibited by Symbiodiniaceae overgrowth. Video Abstract